Hairy Mary: Natal Government Railways 2-8-2 (Tanic Tender Locomotive Havelock) - Hattingh, J.A. (Scientia Militaria - South African Journal of Military Studies, 2012)
This locomotive was actually a Havelock tank Tender-Locomotive with the wheel arrangement of 2-8-2. It was designed in 1887 and built in the Durban workshops. It was the first locomotive to be built in South Africa. It also boasted to be the first locomotive with an eight coupled wheel but was later rebuilt as a 4-6-2.